2013
DOI: 10.1063/1.4804361
|View full text |Cite
|
Sign up to set email alerts
|

High thermal stability of optical transparency in cellulose nanofiber paper

Abstract: Cellulose nanopapers have been shown to maintain high optical transparency after high temperature heating at 150 °C. High temperature heating to around 150 °C is inevitable in electronic device processing. If a polyethylene terephthalate film is held at 150 °C for tens of minutes, cyclic oligomers migrate to the film surface, causing surface roughness that decreases the film transparency. However, because cellulose nanofibers have high thermal stability, the transparent nanopapers maintained their smooth surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 18 publications
3
49
0
Order By: Relevance
“…The increased transparency is due to capillary action during water evaporation from the sheets causing the fibres to be densely packed together allowing more light to pass through the sheets. In addition the surface roughness is also reduced (Nogi et al, 2013). Mechanical properties of paper sludge nanopapers were found to be similar to a previous study on nanocellulose derived from dissolving cellulose sludge (Jonoobi et al, 2012); data are shown in Table 2.…”
Section: Optical Properties Of Paper Sludge Nanofibressupporting
confidence: 85%
“…The increased transparency is due to capillary action during water evaporation from the sheets causing the fibres to be densely packed together allowing more light to pass through the sheets. In addition the surface roughness is also reduced (Nogi et al, 2013). Mechanical properties of paper sludge nanopapers were found to be similar to a previous study on nanocellulose derived from dissolving cellulose sludge (Jonoobi et al, 2012); data are shown in Table 2.…”
Section: Optical Properties Of Paper Sludge Nanofibressupporting
confidence: 85%
“…Recently, cellulose nanofiber (CNF) films have been developed from various phytomass resources and have been shown to exhibit high transparency [28,29] and minimal surface roughness [30,31], as well as good flexibility. Compared with conventional plastics, CNF films are also known to display high strength [32,33] and thermal stability (a low coefficient of thermal expansion) [34,35], owing to the extended chain crystals of natural cellulose type I.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transparent paper made of CNs (NCC and NFC) had a representative thickness of 25-100 μm and a density of 0.8-1.5 g cm −3 , and attracted great attention because of its unique properties such as excellent flexibility [3,5,6,8,[89][90][91][92], superior surface smoothness [7,8,91], thermal stability [93,94], high optical transmittance [5,8,15,43,94,95], strong tensile strength [44,45,[47][48][49] and superior gas barrier performance in dry conditions [51-53, 87, 96-99]. These fascinating properties meet the stringent requirements of fabricating next generation 'green', transparent and flexible electronics on nanopaper.…”
Section: Nanopapermentioning
confidence: 99%